Professional learning as policy enactment: The primacy of professionalism - Hardy, Ian J.; Melville, Wayne (Education Policy Analysis Archives, 2019)
In this article, we draw upon notions of occupational professionalism and organizational professionalism to interrogate the complex, and sometimes contradictory, teacher learning practices that characterize educational policy enactment. We apply these understandings to the Growing Success assessment and evaluation policy in Ontario, Canada, and in relation to how five educators in varied positions in a regional school district made sense of this policy through professional learning. Our research considers how the interactions between professionalism and teacher learning can be deployed to better understand policy enactment as part of educators’ work and learning. The research reveals that organizational professionalism, characterized by hierarchical modes of decision-making, standardized work practices, external regulation and accountability processes, limited teachers’ learning. However, at the same time more occupational professionalism cultivated forms of professional learning necessary for productive enactment of educational policy. In relation to teacher learning for policy enactment, more occupational professionalism was characterized by, inter alia, commitment to student learning, the generation of dialogue about teachers’ assessment practices, coherence in relation to the whole reform agenda, a focus upon the immediacy of practice, and accountability to one another. The research indicates that even as more organizational professionalism is clearly evident in policy reform, the occupational cultures fostered by districts and schools can have significant beneficial effects for how teacher learning is expressed as a form of policy enactment.